Body perfect - Streb, Kirk.; Hayes, Bill.; Wyk, Judy Van.; Quattrone, Kathy; Grassie, John.; Stozier, Henry; Discovery Channel (Firm).; Advanced Medical Productions, Inc. ([S.l.] Discovery Health Media, 2000)
This program tells the latest in cosmetic surgery. From ultrasonic liposuction to anatomical implants to a full body lift, Body Perfect travels the globe to profile patients and surgeons before, during and after their cosmetic procedures.
Series producer, Bill Hayes ; associate producer, Judy Van Wyk ; for Discovery Health Channel, executive in charge of production, Kathy Quattrone ; executive producer, John Grassie.
Narrator, Henry Stozier.
Keywords: Surgery, Plastic; Reconstructive Surgical Procedures; Beauty, Personal